High Resolution Analysis of the SO2 Spectra in the Region of 2600 - 2900 cm-1: 2v3, v2+2v3-v2, and 2v1+v2 Bands - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Bolotova I. B. Irina Batorovna; Konov I. A.; Horneman V.-M.; Leroy K. A. Klod (Claude) Andre (2012, 2012)
Title screen